Nominalization in Russian: eventuality types and aspectual properties - Pazel'skaya, Anna; Tatevosov, Sergei (Proceedings of the Amsterdam Colloquium, 2003)
The paper surveys aspectual classes of deverbal nouns in -nije/tije in Russian. The most puzzling phenomenon is that there is a class of nouns that allow, unlike corresponding verbs, for both telic and atelic interpretations. The analysis of this phenomenon consists of two parts. For imperfective-based nominals, a hybrid aspectual behaviour is explained by assuming the IPFV operator that maps events from the original extension of a verbal predicate into their non-necessarily proper parts. For 'perfective-based' nouns, the vast majority of which are degree achievements, we suggest, first, that stems they are clerived from are not perfective, and, secondly, assume that their telicity is determined by the difference value associated with a property that undergoes change in the course of the event.